KENDALA MASYARAKAT DALAM MENINGKATKAN PRODUKTIVITAS PEMBIBITAN TANAMAN KAKAO DI KANAGARIAN PANYAKALAN KECAMATAN KUBUNG KABUPATEN SOLOK - Yendra, Nofri; Rianto, M.Pd, Slamet; SE, M.Si, Nefilinda (Pendidikan Geografi, 2014)
ABSTRACTÂ This study aims to gain an overview of the constraints of society in improving the productivity of the cocoa plants nurseries views of: 1) knowledge 2) nursery 3) marketing.Based on the results of the data analysis and discussion of matters concluded as follows: 1) knowledge of the community in omprovingthe cocoa plants nurseries, societies have much to learn from older people earlier how the maintenance process. 2) to get the seeds planted in kanagarian panyakalan increasing the productivity of the cocoa plants nurseries, many people have been put on the official seeds obtained from the agency or agencies that guaranteed quality. 3) attempts produktivita cocoa plant nurseries in kanagarian panyakalan, the marketing procces is done by means of a tender or ordering.